Trichome-Related Mutants Provide a New Perspective on Multicellular Trichome Initiation and Development in Cucumber (Cucumis sativus L) - Liu, Xingwang; Bartholomew, Ezra; Cai, Yanling; Ren, Huazhong (Frontiers in Plant Science, 2016)
Trichomes are specialized epidermal cells located in aerial parts of plants that function in plant defense against biotic and abiotic stresses. The simple unicellular trichomes of Arabidopsis serve as an excellent model to study the molecular mechanism of cell differentiation and pattern formation in plants. Loss-of-function mutations in Arabidopsis thaliana have suggested that the core genes GL1 (which encodes a MYB transcription factor) and TTG1 (which encodes a WD40 repeat-containing protein) are important for the initiation and spacing of leaf trichomes, while for normal trichome initiation, the genes GL3 and EGL3 (which encode a bHLH protein) are needed. However, the positive regulatory genes involved in multicellular trichrome development in cucumber remain unclear. This review focuses on the phenotype of mutants (csgl3, tril, tbh, mict and csgl1) with disturbed trichomes in cucumber and then infers which gene(s) play key roles in trichome initiation and development in those mutants. Evidence indicates that MICT, TBH and CsGL1 are allelic with alternative splicing. CsGL3 and TRIL are allelic and override the effect of TBH, MICT and CsGL1 on the regulation of multicellular trichome development; and affect trichome initiation. CsGL3, TRIL, MICT, TBH and CsGL1 encode HD-Zip proteins with different subfamilies. Genetic and molecular analyses have revealed that CsGL3, TRIL, MICT, TBH and CsGL1 are responsible for the differentiation of epidermal cells and the development of trichomes. Based on current knowledge, a positive regulator pathway model for trichome development in cucumber was proposed and compared to a model in Arabidopsis. These data suggest that trichome development in cucumber may differ from that in Arabidopsis.